2011
DOI: 10.1007/s00210-011-0601-6
|View full text |Cite
|
Sign up to set email alerts
|

The vasorelaxant effect of hydrogen sulfide is enhanced in streptozotocin-induced diabetic rats

Abstract: Hydrogen sulfide (H₂S) is an endogenous gas which has potent relaxant effect in vascular and nonvascular smooth muscles. In the present study, we have investigated how streptozotocin (STZ)-induced diabetes affected the relaxant effect of H₂S in rat isolated thoracic aorta and mesenteric and pulmonary arteries. Diabetes was induced by IV injection of STZ (35 mg/kg). Insulin treatment was applied by using insulin implants. At the end of 4 and 12 weeks, the thoracic aorta and mesenteric and pulmonary arteries wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…It is now apparent that H 2 S biosynthesis declines as the severity of diabetes increases over time, and that therapies based on administration of different H 2 S donors to animals or patients in different stages of type I or type II diabetes may be highly successful (19,46,109,221). Interestingly, it has been reported that plasma H 2 S levels are reduced in overweight individuals, with increasing adiposity being a major determinant of said levels (221).…”
Section: Diabetes and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now apparent that H 2 S biosynthesis declines as the severity of diabetes increases over time, and that therapies based on administration of different H 2 S donors to animals or patients in different stages of type I or type II diabetes may be highly successful (19,46,109,221). Interestingly, it has been reported that plasma H 2 S levels are reduced in overweight individuals, with increasing adiposity being a major determinant of said levels (221).…”
Section: Diabetes and Metabolismmentioning
confidence: 99%
“…and disease is clearly borne out by the correlations found to exist between low levels of plasma/tissue endogenous H 2 S/sulfane sulfur and/or H 2 S-generating enzymes on the one hand, and on the other the presence and progression of adiposity, marked endothelial dysfunction/insulin resistance, hypertension, hyperhomocysteinemia, diabetes, exacerbated cardiac injury following ischemia-reperfusion injury, Alzheimer disease, cirrhosis, chronic kidney disease, GI tract irritation, asthma, wound healing, and cancer (19,46,57,58,62,85,109,156,159,210,211,219,221,239).…”
mentioning
confidence: 99%
“…Several studies suggest that streptozotocin (STZ)-induced diabetes (model of type 1 diabetes) increases the expression of CSE and CBS in the pancreas, kidney, and liver (36,37). In contrast, additional studies found that STZ does not alter the expression of either enzyme in the aorta, liver, kidney, or heart (4,27). Despite this contrasting evidence about the effects of STZ-induced diabetes on the expression of CSE and CBS, there is clear evidence that circulating levels of H 2 S are decreased in animal models of diabetes (12,27,37) and may even contribute to the pathophysiology of diabetes (28).…”
mentioning
confidence: 99%
“…Previous studies had reported the involvement of various K þ channels in the vasodilatation induced by H 2 S or it putative donor, NaHS. For instance, in rat mesenteric, aortic and pulmonary arteries as well as in the human internal mammary arteries, blockade of K ATP channels with glibenclamide were shown to attenuate NaHS induced relaxations (Cheng et al, 2004;Denizalti et al, 2011;Sun et al, 2011;Webb et al, 2008;Zhao et al, 2001). Moreover, similar reductions were observed in either H 2 S-or NaHS-induced relaxations with the coapplication of IK Caþþ /BK Caþþ and SK Caþþ channel inhibitors, namely charybdotoxin and apamin, particularly in the endothelium intact mesenteric arteries and thereby, H 2 S was proposed to be a potential mediator of EDHF (Cheng et al, 2004;Mustafa et al, 2011;Zhao and Wang, 2002).…”
Section: Discussionmentioning
confidence: 99%